UPAYA GURU BIMBINGAN DAN KONSELING DALAM MENGATASI MASALAH KECANDUAN GAME ONLINE BAGI SISWA DI SMAN 1 BONJOL KABUPATEN PASAMAN - Winni Yunika Putri; Sri Hartati; Yeni Afrida; M Arif (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The main problem in this study is that many students at SMAN 1 Bonjol Pasaman are currently addicted to playing online games. During recess they play a lot of online games and it's even difficult to control them bringing their cellphones into class. When playing online games they are careless and do not know the circumstances around them, sometimes they don't even know that recess is over and they return to class to study. Therefore, guidance and counseling teachers have made various efforts to overcome online game addiction among students. This research is a field research (field research), namely research conducted in a location, a large room or in the midst of society. The research method used is a qualitative descriptive method, namely research that aims to describe systematically, factually, and accurately the facts and characteristics of certain populations to try to describe the phenomenon in detail. The key informant in this study was the Guidance Teacher Coordinator. While the supporting informants are the principal and his representatives, counseling teachers, subject teachers and students and students. In collecting the data needed by the author using interviews and observation. The results of the study can be described as the efforts of the counseling teacher in overcoming online game addiction among students at SMAN 1 Bonjol; 1) Trying to understand the various types of online games and their negative impacts, 2) Working closely with subject teachers and parents of students in overcoming and preventing online game problems. and 3) Increasing various extracurricular activities at school, both activities in the religious field and activities in other fields. Based on the data above, it can be concluded that the counseling teachers at SMAN 1 Bonjol Pasaman have made various efforts to overcome online game addiction by students through various counseling services.